Center of excellence assistance model: Is it effective to improve vocational school management in Central Java? - Sucipto, Sucipto; Arief, Sandy; Susanti, Anis (LPMPP Universitas Negeri Yogyakarta, 2024)
The Centre of Excellence Vocational High School (CEVHS) is a program to develop vocational education and prepare students with skills more relevant to society's needs, which are constantly changing according to industry, business, and workplace developments. This research aimed to analyze the Centre of Excellence's assistance effectiveness in improving the quality of vocational school management in Central Java. Through a quantitative approach, this study involved CEVHS teachers in Central Java from a sample of 21 CEVHSs assisted by lecturers from Universitas Negeri Semarang. The data were collected through a questionnaire and analysed using the t-test. The test results indicate sig 0.000 < 0.05, meaning that the resulting value has experienced Very Good development. Therefore, there is a positive relationship before and after mentoring at CEVHSs, and CEVHS needs assistance in managing the school and improving school quality. More attention and supervision while implementing assistance is vital to enhance vocational school management.